The Relationship Between Anaphor Features and Antecedent Retrieval: Comparing Mandarin Ziji and Ta-Ziji - Dillon, Brian (Front Psychol, 2016)
In the present study we report two self-paced reading experiments that investigate antecedent retrieval processes in sentence comprehension by contrasting the real-time processing behavior of two different reflexive anaphors in Mandarin Chinese. Previous work has suggested that comprehenders initially evaluate the fit between the morphologically simple long-distance reflexive “ziji” and the closest available subject position, only subsequently considering more structurally distant antecedents (Gao et al., 2005; Liu, 2009; Li and Zhou, 2010; Dillon et al., 2014; cf. Chen et al., 2012). In this paper, we investigate whether this locality bias effect obtains for other reflexive anaphors in Mandarin Chinese, or if it is associated specifically with the morphologically simple reflexive ziji. We do this by comparing the processing of ziji to the processing of the morphologically complex reflexive ta-ziji (lit. s/he-self). In Experiment 1, we investigate the processing of ziji, and replicate the finding of a strong locality bias effect for ziji in self-paced reading measures. In Experiment 2, we investigate the processing of the morphologically complex reflexive ta-ziji in the same structural configurations as Experiment 1. A comparison of our experiments reveals that ta-ziji shows a significantly weaker locality bias effect than ziji does. We propose that this results from the difference in the number of morphological and semantic features on the anaphor ta-ziji relative to ziji. Specifically, we propose that the additional retrieval cues associated with ta-ziji reduce interference from irrelevant representations in memory, allowing it to more reliably access an antecedent regardless its linear or structural distance. This reduced interference in turn leads to a diminished locality bias effect for the morphologically complex anaphor ta-ziji.